Current Perspectives on Role of MSC in Renal Pathophysiology - Fan, Min; Zhang, Jing; Xin, Hong; He, Xiaozhou; Zhang, Xuemei (Frontiers in Physiology, 2018)
In the course of the development and worsening of kidney disease, renal fibrosis is an almost inevitable and irreversible end-stage process. Currently, the only treatments available to ameliorate this disease include hemodialysis, peritoneal dialysis, and kidney transplantation; however, these are expensive and may cause adverse effects such as immune rejection, inadequate renal resources, or post-operative complications. Therefore, there is an urgent need to develop more effective treatments. The advent of mesenchymal stem cells (MSCs) represents a new direction in this context. Because of extensive studies conducted on adult stem cells and biological characteristics of MSCs in regenerative medicine, therapeutic strategies using MSCs have recently been widely used in the treatment of fibrotic and other kidney diseases. This review is focused on the treatment of renal fibrosis using MSCs based on studies conducted in the recent years.